Bipolar membrane and preparation and use method thereof
By using sulfonated polymer monomers, sulfonic acid ionic liquids, quaternized imidazole derivatives and quaternary ammonium ionic liquids in the bipolar membrane, combined with the design of the metal catalyst layer, the problem of low acid and alkali production of bipolar membranes is solved, and stable production and long-term application of high concentrations of acid and alkali are achieved.
Patent Information
- Application Number
- CN202411663193.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing bipolar membrane has a low concentration when producing acid and alkali, which limits the reuse of acid and alkali and the application development of bipolar membranes.
A bipolar membrane is adopted, and the cation exchange membrane and anion exchange layer contain sulfonated polymer monomers and sulfonic acid ionic liquids, as well as quaternized imidazole derivatives and quaternary ammonium ionic liquids, respectively. The ion exchange capacity of the film is increased by adding ionic liquids, and a metal catalyst layer is added to the process to enhance the tolerance of the film.
It significantly improves the concentration and yield of acid and base, reduces the demand for subsequent concentration, reduces the process and cost, and improves the stability and life of the membrane.
Smart Images

Figure BDA0005143967300000182 
Figure BDA0005143967300000191 
Figure BDA0005143967300000201
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of electrodialysis membranes, and in particular to a bipolar membrane and a preparation and use method thereof. Background Art
[0002] The bipolar membrane is a special ion exchange membrane, which usually contains a cation exchange layer and an anion exchange layer. The characteristic of this membrane is that under the action of a DC electric field, the H2O between the anion and cation membrane layers dissociates into H+ and OH- and passes through the anion membrane and the cation membrane respectively, serving as the source of H+ and OH- ions. That is, when the bipolar membrane is subjected to a reverse voltage, water decomposes in the interface layer of the bipolar membrane, decomposing to generate H+ and OH- and then migrates into the solution through the anion and cation membranes. This bipolar membrane realizes the dissociation of water to generate H + and OH - The process is simple and produces little waste, and it has good prospects in the fields of water electrolysis to produce hydrogen and carbon dioxide reduction. At the same time, bipolar membranes have also been widely used in the preparation of inorganic acids and bases such as sodium sulfate, sodium chloride, lithium sulfate, lithium chloride, and sodium nitrate.
[0003] With the exploration in the field of organic acids and organic bases, many application cases and scenarios of bipolar membranes have been developed, such as formic acid (Ferrer J, et al, 2006a), acetic acid (YUL, et al, 2003a), lactic acid (Lee E, et al, 1998; Li H, et al, 2004), citric acid (Novalic S. and Kulbe K, 1998a; Pinacci P. and Radaeli M, 2002), β-aminopropionic acid (CN 109851515 B), tetramethylammonium hydroxide, etc.; However, in the above-mentioned bipolar membrane conversion projects of inorganic salts or organic acids and bases that have been disclosed, considering the energy consumption and the acid and alkali production capacity and tolerance of the bipolar membrane itself, the acid and alkali concentrations usually prepared are between 1-2N, which greatly limits the reuse of acids and alkalis and the development of bipolar membrane applications. Taking the scheme disclosed in Chinese patent application CN109851515A as an example, the method uses 3-aminopropionitrile and sodium hydroxide aqueous solution as raw materials, reacts to obtain 3-aminopropionic acid sodium solution, and then directly converts 3-aminopropionic acid sodium into sodium hydroxide and product β-aminopropionic acid through bipolar membrane electrodialysis; because the preceding 3-aminopropionitrile needs to be mixed with a sodium hydroxide aqueous solution with a concentration of 32%, and the alkali concentration produced by conventional bipolar membrane electrodialysis is 8%, it needs to be subsequently concentrated to meet the conditions for reuse, which increases the processing steps and costs of acid and alkali reuse. For the bipolar membrane conversion process of preparing high-purity lithium hydroxide by dissolving lithium carbonate with inorganic acids and alkalis such as sulfuric acid, the cost and site requirements of the subsequent concentration process are also greatly increased due to the limitation of the acid and alkali concentration prepared by the bipolar membrane itself. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is the defect of low acid and alkali concentration of the currently disclosed bipolar membrane, so as to provide a bipolar membrane that effectively improves the acid and alkali concentration and a preparation and use method thereof.
[0005] A bipolar membrane comprising:
[0006] A cation exchange membrane comprises a substrate and a cation exchange layer disposed on at least one surface of the substrate, wherein the cation exchange layer comprises a sulfonated polymer monomer and a sulfonic acid type ionic liquid, wherein the sulfonic acid type ionic liquid accounts for more than 10% by weight of the sulfonated polymer monomer; preferably, the sulfonic acid type ionic liquid accounts for 10%-20% by weight of the sulfonated polymer monomer, for example, the sulfonic acid type ionic liquid accounts for 10%, 12%, 14%, 16%, 18%, 20%, 20%, etc. of the weight of the sulfonated polymer monomer;
[0007] The metal catalyst layer is disposed on one surface of the substrate so that the two opposite surfaces of the substrate are respectively a cation exchange layer and a metal catalyst layer;
[0008] The anion exchange layer is arranged on the surface of the metal catalyst layer, which includes quaternized imidazole derivatives and quaternary ammonium ionic liquids, wherein the quaternary ammonium ionic liquid is more than 25% by weight of the imidazole derivatives; preferably, the quaternary ammonium ionic liquid is 25%-60% by weight of the imidazole derivatives, for example: the quaternary ammonium ionic liquid is 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% and the like by weight of the imidazole derivatives.
[0009] The cation exchange layers are arranged on both surfaces of the substrate, and the metal catalyst layer is arranged on the surface of one of the cation exchange layers.
[0010] The cation exchange layer is made of cross-linked sulfonated polymer monomers mixed with sulfonic acid ionic liquids, and the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer is 1:(7-12), preferably 1:(9-10); for example, the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer is 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12, etc.
[0011] And / or, the degree of ammonium of the quaternized imidazole derivative is 40-85%, for example, the degree of ammonium of the quaternized imidazole derivative is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.;
[0012] And / or, the mesh number of the substrate is 120-260 mesh, for example, the mesh number of the substrate is 120 mesh, 140 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 240 mesh, 260 mesh, etc.;
[0013] And / or, the loading amount of the metal catalyst layer on the substrate is 0.5-5 g / m 2 , preferably 1-1.5g / m 2 ; For example: the loading amount of the metal catalyst layer is 0.5g / m 2 , 1g / m 2 , 1.5g / m 2 , 2.0g / m 2 , 2.5g / m 2 3.0g / m 2 3.5g / m 2 4.0g / m 2 4.5g / m 2 , 5g / m 2 wait;
[0014] And / or, the thickness of the anion exchange layer is 30-80 μm; for example, the thickness of the anion exchange layer is 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, or 80 μm.
[0015] The sulfonic acid ionic liquid is selected from one or more of 1-propylsulfonic acid-3-methylimidazolium chloride (CAS: 1034558-51-4) and 1-propylsulfonic acid-3-vinylimidazolium chloride (CAS: 1416152-27-6);
[0016] And / or, the sulfonated polymer monomer is a sulfonated polystyrene monomer;
[0017] And / or, the quaternary ammonium ionic liquid is selected from one or more of butyltrimethylammonium chloride, hexyltrimethylammonium chloride, propyltrimethylammonium bromide, tetrapropylammonium hydrogen sulfate, tetraoctylammonium bromide and butyltriethylammonium bromide (CAS: 13028-69-8);
[0018] And / or, the imidazole derivatives include 2-methyl-1-vinyl imidazole or 1,2-dimethyl imidazole; in the present invention, quaternary ammonium groups are used as exchange groups of the anion exchange membrane layer, therefore, the degree of ammoniation here refers to: the ratio of the halogenated hydrocarbons on the polymer to the tertiary amines reacting to form quaternary ammonium salts.
[0019] And / or, the substrate is selected from any one of nylon mesh, PET mesh, PP mesh, PVC mesh, and PE mesh;
[0020] And / or, the catalyst in the metal catalyst layer is a metal salt, preferably a water-soluble metal salt, more preferably a water-soluble metal chloride. The metal in the metal salt includes one or more of titanium (Ti), tin (Sn), chromium (Cr), cobalt (Co), nickel (Ni), platinum (Pt), silver (Ag), or ruthenium (Ru).
[0021] A method for preparing a bipolar membrane, comprising:
[0022] Preparation of cation exchange membrane: prepare the raw materials of cation exchange layer into membrane-building liquid, prepare the membrane-building liquid on at least one side of the substrate, for example, the membrane-building liquid can be prepared on one side of the substrate, or the membrane-building liquid can be prepared on the entire surface of the substrate, take it out, dry and polymerize it, and cool it to obtain the cation exchange membrane;
[0023] Preparation of the metal catalyst layer: preparing the raw materials for preparing the metal catalyst layer into a suspension, evenly applying the suspension on the other side of the cation exchange membrane with the cation exchange layer, and drying to obtain the metal catalyst layer;
[0024] Preparation of anion exchange layer: prepare the raw materials of anion exchange layer into anion membrane material, attach the anion membrane material to the metal catalyst layer, and obtain a bipolar membrane through ultraviolet light initiation and / or hot pressing reaction.
[0025] In the preparation step of the cation exchange membrane, the raw materials of the cation exchange layer include sulfonated polymer monomers, solvents, crosslinking agents and sulfonic acid ionic liquids, and / or the membrane-building liquid is attached to the substrate by immersion, and / or the drying polymerization process is: first volatilizing at 25-30°C and humidity ≤55% for more than 5 hours, and then drying, preferably, the drying conditions are 100-120°C and more than 24 hours;
[0026] In the preparation step of the metal catalyst layer, the raw materials of the metal catalyst layer include metal salt, quaternary ammonium and acid solution; the preparation process of the suspension liquid is: the metal salt is added with acid solution to coordinate with the quaternary ammonium in a weakly acidic environment of pH 3-5, and the suspension liquid is obtained after ultrasonic treatment; and / or, the suspension liquid is applied on the cation exchange membrane by ultrasonic spraying; and / or, the drying conditions are 100-120°C and 1.5-2h;
[0027] In the preparation step of the anion exchange layer, the raw materials of the anion exchange layer include imidazole derivatives, quaternary ammonium reagents, solvents and quaternary ammonium ionic liquids; the ultraviolet light initiation time is 1-10 minutes; the pressure of the hot pressing reaction is 0.1-0.4MpaG and the temperature is 100-130°C.
[0028] In the preparation step of the cation exchange membrane, the crosslinking agent is selected from one or more polyvinylbenzenes, preferably one or more divinylbenzene, trivinylbenzene, divinyltoluene, and divinylethylbenzene; the total amount of the crosslinking agent is 5-15wt% of the mass of the sulfonated polymer monomer; the amount of the solvent is 1-3 times the total mass of the sulfonic acid ionic liquid and the crosslinking agent; the immersion time is 2-8min;
[0029] In the step of preparing the metal catalyst layer, the acid solution is an inorganic acid, the quaternary ammonium salt is selected to be as close as possible to the quaternary ammonium type in the anion film layer after quaternization of the anion film layer, for example: trimethylpropylammonium bromide (CAS: 2650-50-2), etc., the ultrasonic spraying uses a fan-shaped ultrasonic atomizing nozzle or a vortex ultrasonic atomizing nozzle, the input gas source pressure of the ultrasonic spraying is 0.5-0.8Mpa, and the operating speed is <900mm / s;
[0030] In the preparation step of the anion exchange layer, the content of the imidazole derivative and the quaternary ammonium agent is 15-50% of the solvent content, preferably 15-35%, for example, the content of the imidazole derivative and the quaternary ammonium agent is 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. of the solvent content; the quaternary ammonium agent includes any one of bromopropane, chloropropane, iodomethane, and 1,4-dichlorobutane; and / or, the molar ratio of the quaternary ammonium ionic liquid to the imidazole derivative is 1:(5-12), for example, the molar ratio of the quaternary ammonium ionic liquid to the imidazole derivative is 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, etc.;
[0031] The solvent is selected from one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC) and N-methylpyrrolidone (NMP), preferably N,N-dimethylformamide (DMF).
[0032] The method of using the bipolar membrane includes:
[0033] The bipolar membrane is installed in a three-compartment bipolar membrane electrodialysis membrane device or a two-compartment electrodialysis device with mature commercial anion exchange membrane and cation exchange membrane for application in the fields of lithium extraction from salt lakes, waste salt resource utilization, material purification or recovery of organic acids and alkalis.
[0034] Three-compartment bipolar membrane electrodialysis device or two-compartment electrodialysis device is suitable for the preparation and recovery of high-concentration acids and alkalis. The current density during use is 400-1000A / m 2 , preferably 600-1000A / m 2 , the concentration of the salt chamber is maintained between 2.5-1.1N (equivalent concentration N is 2.5-1.1), the conductivity of the organic acid / organic base chamber in the two-compartment bipolar membrane system is sufficient to maintain the full current state under the operating current density, and the water inlet conditions meet the water inlet requirements of conventional bipolar membrane electrodialysis;
[0035] And / or, the operating pressure is less than 0.1 MPa, and / or, the operating temperature is 25-45°C, and / or, the membrane surface flow rate during operation is 3-9 cm / s, preferably 5-9 cm / s.
[0036] The operating temperature is 30-40℃.
[0037] The technical solution of the present invention has the following advantages:
[0038] 1. The bipolar membrane provided by the present invention can maximize the cation exchange membrane and the anion exchange layer for H by adding ionic liquid. + and OH - The selective permeability of the bipolar membrane anion and cation exchange membrane is increased, thereby increasing the ion exchange capacity of the bipolar membrane anion and cation exchange membrane, thereby increasing the acid and alkali concentration and yield obtained in the application; at the same time, monomers with strong tolerance under acidic and alkaline conditions are further selected to enhance the acid and alkali tolerance effect, and then the bonding effect of the anion and cation exchange membrane is enhanced by ultraviolet light initiation and / or hot pressing, etc., to ensure the life and stability of the bipolar membrane, and with the support of the main structure of the substrate, it has the advantages of stable membrane structure, high acid and alkali concentration, stable performance, etc., and is suitable for long-term and stable preparation of high-concentration acid and alkali. The implementation mechanism of the present invention is as follows:
[0039] The study found that the main reason for the limitation of acid-base concentration is that the H generated by the bipolar membrane during the water dissociation process + and OH - There is a certain limit to the transmission rate through the cation exchange membrane and anion exchange layer of the corresponding bipolar membrane. Therefore, under a fixed current, the generated H + and OH - , the amount of water that passes through the cation exchange membrane and anion exchange layer corresponding to the bipolar membrane is small, resulting in low efficiency; therefore, when the water dissociation voltage of the bipolar membrane is fixed, the amount of acid / base produced per unit energy consumption is small and the concentration is low. The Vehicle mechanism believes that: protons combine with carriers, and under the action of electroosmosis, concentration difference, and pressure difference, they diffuse and transfer in the form of hydronium ions; this diffusion process is called proton transfer. In solution, protons usually combine with water molecules to form hydronium ions, which can be free between water molecules and between negatively charged carriers. When the charge carrier combines with the hydronium ion to form a proton-charge carrier complex, the charge carrier can transfer protons through its transfer. Hydrogen ions and hydroxide ions realize charge transfer by vibrating hydrogen bonds between water molecules, not as a whole, so the faster the migration, the greater the mobility, and H + The mobility is 32.5×10 -4 cm·sec -1 , OH - The mobility is 17.8×10 -4 cm·sec -1 . The mobility of other ions is less than 6×10 -4 cm·sec -1 In comparison, H + With OH -Ions have a very large ion migration rate. The higher the fixed ion concentration in the membrane, the higher the selective permeability of the membrane to counterions, which helps H + With OH - Rapid migration increases the corresponding acid and base concentration and yield. Therefore, the present invention can effectively increase the fixed ion concentration in the membrane by adding a specific type of ionic liquid to the bipolar membrane, thereby increasing the acid and base concentration and yield obtained in the application;
[0040] In addition, bipolar membranes are used in high electric field and strong acid and alkali environments, and they also need to have stability and lifespan suitable for relatively high concentrations of acid and alkali. Studies have found that in alkaline environments, the side chain cations of the polymer skeleton are easily affected by OH - Attack, nucleophilic substitution, Hofmann degradation and Ylide reaction occur. Therefore, the present invention effectively blocks OH by adding ionic liquid. - The attack on the side chain cations effectively improves the stability of high-concentration acids and bases and the binding capacity of anion and cation exchange membranes, thereby ensuring the stability of bipolar membrane applications.
[0041] 2. In the method for using a bipolar membrane provided by the present invention, the bipolar membrane can be used for conventional two-compartment and three-compartment bipolar membrane electrodialysis. With sufficient electrolyte, the acid-base concentration generated at a certain current density can be greater than 4N, and it has the advantages of low energy consumption, long-term stable performance and long life. DETAILED DESCRIPTION
[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0044] Source of raw materials: Sulfonated polystyrene, manufacturer Qiyue Biological; 1-propylsulfonic acid-3-methylimidazolium chloride, 1-propylsulfonic acid-3-vinylimidazolium chloride, hydroxypropyltrimethylammonium chloride, tetraoctylammonium bromide ionic liquids, all manufacturers are Olike New Materials Technology Co., Ltd.
[0045] Example 1
[0046] A method for preparing a bipolar membrane, comprising:
[0047] S1. Preparation of cation exchange membrane
[0048] 700 g of N,N-dimethylformamide (DMF) was added to a reaction kettle, 250 g of sulfonated polystyrene (SPS, about 1.3 mol) and 25.5 g of divinylbenzene were added under stirring, 32 g of 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid (about 0.13 mol) was slowly introduced and fully mixed to form a membrane-building solution, wherein the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer was about 1:10, and a 200-mesh PVC mesh was used for impregnation for 2 min, the solvent was evaporated for 6 h at room temperature with a humidity of ≤55%, and the mixture was placed in a 100° C. oven for drying for 24 h, and after being taken out and cooled to room temperature, a cation exchange membrane having a cation exchange layer was obtained;
[0049] S2. Preparation of metal catalyst layer
[0050] Take 4g of hydroxypropyltrimethylammonium chloride and 10g of tin dichloride and adjust the pH to 3 with hydrochloric acid to form a suspension. Use a fan-shaped ultrasonic atomizing nozzle to set the input gas source pressure to 0.65Mpa and the running speed to 500mm / s for spraying. Spray the suspension on the surface of the cation exchange membrane described in S1 in the above-mentioned setting manner. The spraying amount is 1.1g / m based on the weight of the metal catalyst layer finally formed. 2 , and then placed it in an oven at 120°C to dry for 2 hours, to obtain a metal catalyst layer on the basis of the cation exchange membrane;
[0051] Preparation of S3 anion exchange layer
[0052] Weigh 200g of dried 2-methyl-1-vinyl imidazole and 100g of bromopropane on a balance, mix them, dissolve them in 800g of N,N-dimethylformamide (DMF) and polymerize them at 55°C, slowly introduce 120g of tetraoctylammonium bromide ionic liquid into them, stir them evenly for quaternization, control the degree of ammoniumization at 80%, and obtain an anion membrane material; evenly scrape the anion membrane material on one side of a cation exchange membrane containing a metal catalyst layer, with a scraping thickness of 50μm, initiate them with ultraviolet light at 275nm for 5min, take them out and place them in a hot press, at a temperature of 100°C and a pressure of 0.2MPaG, and take them out after hot pressing for 2h to obtain a bipolar membrane suitable for high-concentration acids and bases.
[0053] Activation of bipolar membrane: Place the bipolar membrane in a commercial cation / cation membrane group to form a membrane stack (the bipolar membrane and the commercial cation / cation membrane together form a membrane stack device), in a 15% sodium sulfate aqueous solution, the current density is 800A / m 2 The DC electric field was maintained for 1 h, and each compartment was rinsed clean with deionized water.
[0054] The activated bipolar membrane group of the present invention can be used to recycle high-concentration acid and alkali. During use, the operating pressure is 0.05MPa, the operating temperature is 35°C, the operating membrane surface flow rate is 6cm / s, and the operating current density is 800A / m 2 .
[0055] Example 2
[0056] A method for preparing a bipolar membrane, comprising:
[0057] Preparation of S1 cation exchange membrane
[0058] 750 g of N,N-dimethylformamide (DMF) was added to the reaction kettle, and 250 g of sulfonated polystyrene (SPS, about 1.3 mol) and 30 g of divinyl ethylbenzene were added under stirring, and 25 g of 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid (about 0.10 mol) and 5 g of 1-propylsulfonic acid-3-vinylimidazolium chloride (about 0.02 mol) were slowly introduced and fully mixed to form a membrane-building solution, wherein the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer was about 1:10.8. A 210-mesh PE mesh was used for impregnation for 3 min, the solvent was evaporated at room temperature for 6 h, and the mesh was placed in a 100° C. oven for drying and polymerization for 24 h. After being taken out and cooled to room temperature, a cation exchange layer was obtained;
[0059] Preparation of S2 metal catalyst layer
[0060] Take 4g of hydroxypropyltrimethylammonium chloride and 15g of ruthenium dichloride, adjust the pH to 3 with hydrochloric acid to form a suspension, set the input gas source pressure to 0.8Mpa, and spray at a speed of 700mm / s using a fan-shaped ultrasonic atomizing nozzle. Spray the suspension on the cation exchange membrane described in S1 in the above-mentioned manner, and the spraying amount is 3g / m based on the weight of the metal catalyst layer finally formed. 2 , and then placed it in an oven at 120°C to dry for 2 hours, to obtain a metal catalyst layer on the basis of the cation exchange membrane;
[0061] Preparation of S3 anion exchange layer
[0062] Weigh 215g of dried 2-methyl-1-vinyl imidazole and 87g of bromopropane on a balance, dissolve in 730g of N,N-dimethylformamide (DMF) and polymerize at 55°C, slowly introduce 55g of butyl trimethyl ammonium chloride ionic liquid into it, stir evenly for quaternization, control the degree of ammoniation at 70%, and obtain anion membrane material; evenly scrape the anion membrane material on one side of the cation exchange membrane containing a metal catalyst layer, with a scraping thickness of 45μm, initiate with 275nm, 5min ultraviolet light, take it out and place it in a hot press, at a temperature of 105°C and a pressure of 0.3MPaG, and take it out after hot pressing for 2h to obtain a bipolar membrane suitable for high concentration acid and alkali. Activation of bipolar membrane:
[0063] The bipolar membrane was placed in a commercial cation-cation membrane group to form a membrane stack (the bipolar membrane and the commercial cation-cation membrane together formed a membrane stack device). In a 15% sodium sulfate aqueous solution, the current density was 1000A / m 2 The DC electric field was maintained for 1 h, and each compartment was rinsed clean with deionized water.
[0064] The activated bipolar membrane group of the present invention can be used to recycle high-concentration acid and alkali. During use, the operating pressure is 0.05MPa, the operating temperature is 35°C, the operating membrane surface flow rate is 6cm / s, and the operating current density is 800A / m 2 .
[0065] Example 3
[0066] A method for preparing a bipolar membrane, comprising:
[0067] Preparation of S1 cation exchange membrane
[0068] 700 g of N,N-dimethylformamide (DMF) was added to the reaction kettle, and 220 g of sulfonated polystyrene (SPS, about 1.19 mol) and 27.5 g of trivinyl ethylbenzene were added under stirring, and 22 g of 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid (about 0.09 mol) and 7.5 g of 1-propylsulfonic acid-3-vinylimidazolium chloride (about 0.04 mol) were slowly introduced and fully mixed to form a membrane-building solution, wherein the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer was about 1:9.15. A 210-mesh PVC mesh was used for impregnation for 3 min, the solvent was volatilized at room temperature for 8 h, and the mixture was placed in a 100° C. oven for drying and polymerization for 24 h. After being taken out and cooled to room temperature, a cation exchange layer was obtained;
[0069] Preparation of S2 metal catalyst layer
[0070] Take 4g of hydroxypropyltrimethylammonium chloride and 15.5g of titanium trichloride and adjust the pH to 4 with hydrochloric acid to form a suspension. Use a fan-shaped ultrasonic atomizing nozzle to set the input gas source pressure to 0.6Mpa and the running speed to 700mm / s for spraying. Spray the suspension on the cation exchange membrane described in S1 in the above-mentioned setting manner. The spraying amount is 3g / m based on the weight of the metal catalyst layer finally formed. 2 , and then placed it in an oven at 120°C to dry for 2 hours, to obtain a metal catalyst layer on the basis of the cation exchange membrane;
[0071] Preparation of S3 anion exchange layer
[0072] Weigh 200g of dried 2-methyl-1-vinylimidazole on a balance and mix it with 95g of chloropropane, dissolve it in 750g of N,N-dimethylformamide (DMF) and polymerize it at 55°C, slowly introduce 100g of tetraoctylammonium bromide ionic liquid into it, stir evenly for quaternization, control the degree of ammoniation at 75%, and obtain a negative membrane material; the negative membrane material is evenly scraped on one side of a cation exchange membrane containing a metal catalyst layer, with a scraping thickness of 45μm, and is initiated by ultraviolet light at 275nm for 6min, taken out and placed in a hot press, and hot-pressed at a temperature of 100°C and a pressure of 0.35MPaG for 2h to obtain a bipolar membrane suitable for high-concentration acid and alkali.
[0073] Activation of bipolar membrane: The bipolar membrane was placed in a commercial cation membrane to form a two-compartment membrane stack. The current density was 800 A / m in a 12% sodium chloride aqueous solution. 2 The DC electric field was maintained for 1 h, and each compartment was rinsed clean with deionized water.
[0074] The activated bipolar membrane group of the present invention can be used to recycle high-concentration acid and alkali. During use, its operating pressure is 0.055MPa, the operating temperature is 32°C, the operating membrane surface flow rate is 8cm / s, and the operating current density is 750A / m 2 .
[0075] Example 4
[0076] The method is the same as that in Example 1, except that the amount of tin dichloride added in step S2 is 0.5 g, and other operations and conditions remain unchanged to obtain a bipolar membrane.
[0077] Example 5
[0078] The method is the same as that in Example 1, the only difference is that: referring to the method in Example 1, the only difference is that when preparing the negative film layer, 2-methyl-1-vinylimidazole and bromopropane are replaced with 1,2-dimethylimidazole and 1,4-dichlorobutane, and other operations and conditions remain unchanged.
[0079] Example 6
[0080] The method is the same as that in Example 1, except that the ruthenium dichloride in step S2 is replaced by nickel chloride (NiCl2).
[0081] Example 7
[0082] The method is the same as that of Example 1, except that the current density is 400 A / m 2 , membrane surface flow rate 5cm / s.
[0083] Example 8
[0084] A method for preparing a bipolar membrane, comprising:
[0085] Preparation of S1 cation exchange membrane
[0086] 270 g of N, N-dimethylformamide (DMF) was added to a reaction kettle, and 220 g of sulfonated polystyrene (SPS, 1.19 mol) and 13.5 g of trivinylethylbenzene were added under stirring, and 22 g of 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid (0.09 mol) and 14.85 g of 1-propylsulfonic acid-3-vinylimidazolium chloride (0.069 mol) were slowly introduced and fully mixed to form a membrane-building solution, wherein the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer was about 1:7.5. A 125-mesh PVC mesh was used for impregnation for 8 min, the solvent was volatilized at room temperature for 8 h, and the mixture was placed in a 100° C. oven for drying and polymerization for 24 h. After being taken out and cooled to room temperature, a cation exchange layer was obtained;
[0087] Preparation of S2 metal catalyst layer
[0088] Take 4g of hydroxypropyltrimethylammonium chloride and 15.5g of titanium trichloride and adjust the pH to 4 with hydrochloric acid to form a suspension. Use a fan-shaped ultrasonic atomizing nozzle to set the input gas source pressure to 0.6Mpa and the running speed to 700mm / s for spraying. Spray the suspension on the cation exchange membrane described in S1 in the above-mentioned setting manner. The spraying amount is 3g / m based on the weight of the metal catalyst layer finally formed. 2 , and then placed it in an oven at 120°C to dry for 2 hours, to obtain a metal catalyst layer on the basis of the cation exchange membrane;
[0089] Preparation of S3 anion exchange layer
[0090] Weigh 200 g of dried 2-methyl-1-vinyl imidazole on a balance and mix it with 95 g of chloropropane, dissolve it in 1970 g of N,N-dimethylformamide (DMF) and polymerize it at 55° C. Slowly introduce 100 g of tetraoctylammonium bromide ionic liquid into it, stir it evenly for quaternization, and control the degree of ammoniation at 40% to obtain a negative membrane material; the negative membrane material is evenly scraped on one side of a cation exchange membrane containing a metal catalyst layer, with a scraping thickness of 79 μm, and is initiated by ultraviolet light at 275 nm for 6 minutes. After being taken out, it is placed in a hot press, and is hot-pressed at a temperature of 130° C. and a pressure of 0.35 MPaG for 2 hours to obtain a bipolar membrane suitable for high-concentration acids and bases.
[0091] Activation of bipolar membrane: The bipolar membrane was placed in a commercial cation membrane to form a two-compartment membrane stack. The current density was 400 A / m in a 12% sodium chloride aqueous solution. 2 The DC electric field was maintained for 1 h, and each compartment was rinsed clean with deionized water.
[0092] The activated bipolar membrane group of the present invention can be used to recycle high-concentration acid and alkali. During use, its operating pressure is 0.055MPa, the operating temperature is 32°C, the operating membrane surface flow rate is 8cm / s, and the operating current density is 750A / m 2 .
[0093] Example 9
[0094] A method for preparing a bipolar membrane, comprising:
[0095] S1. Preparation of cation exchange membrane
[0096] Add 690g N,N-dimethylformamide (DMF) into a reaction kettle, add 200g sulfonated polystyrene (SPS, about 1.085mol) and 30g divinylbenzene under stirring, slowly introduce 22.9g 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid (about 0.095mol) and mix thoroughly to form a membrane-building solution, wherein the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer is about 1:11.4, and 260 mesh PVC mesh is used for impregnation for 2min, the solvent is evaporated for 6h at room temperature with a humidity of ≤55%, and then placed in a 100°C oven for drying for 24h, and taken out and cooled to room temperature to obtain a cation exchange membrane with a cation exchange layer;
[0097] S2. Preparation of metal catalyst layer
[0098] Take 4g of hydroxypropyltrimethylammonium chloride and 10g of tin dichloride and adjust the pH to 3 with hydrochloric acid to form a suspension. Use a fan-shaped ultrasonic atomizing nozzle to set the input gas source pressure to 0.65Mpa and the running speed to 500mm / s for spraying. Spray the suspension on the surface of the cation exchange membrane described in S1 in the above-mentioned setting manner. The spraying amount is 1.1g / m based on the weight of the metal catalyst layer finally formed. 2 , and then placed it in an oven at 120°C to dry for 2 hours, to obtain a metal catalyst layer on the basis of the cation exchange membrane;
[0099] Preparation of S3 anion exchange layer
[0100] Weigh 200g of dried 2-methyl-1-vinyl imidazole and 100g of bromopropane on a balance, mix them, dissolve them in 600g of N,N-dimethylformamide (DMF) and polymerize them at 55°C, slowly introduce 120g of tetraoctylammonium bromide ionic liquid into them, stir them evenly for quaternization, control the degree of ammoniumization at 85%, and obtain an anion membrane material; evenly scrape the anion membrane material on one side of a cation exchange membrane containing a metal catalyst layer, with a scraping thickness of 50μm, initiate them with ultraviolet light at 275nm for 5min, take them out and place them in a hot press, at a temperature of 100°C and a pressure of 0.2MPaG, and take them out after hot pressing for 2h to obtain a bipolar membrane suitable for high-concentration acids and bases.
[0101] Activation of bipolar membrane: Place the bipolar membrane in a commercial cation / cation membrane group to form a membrane stack (the bipolar membrane and the commercial cation / cation membrane together form a membrane stack device), in a 15% sodium sulfate aqueous solution, the current density is 1000A / m 2 The DC electric field was maintained for 1 h, and each compartment was rinsed clean with deionized water.
[0102] The activated bipolar membrane group of the present invention can be used to recycle high-concentration acid and alkali. During use, the operating pressure is 0.05MPa, the operating temperature is 35°C, the operating membrane surface flow rate is 9cm / s, and the operating current density is 800A / m 2 .
[0103] Comparative Example 1
[0104] The method is the same as that in Example 1, except that: no 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid is added when preparing the S1 cation exchange membrane, and no tetraoctylammonium bromide ionic liquid is added when preparing the anion exchange layer in S3. Other operations and conditions remain unchanged to obtain a bipolar membrane.
[0105] Comparative Example 2
[0106] The method is the same as that in Example 1, the only difference is that 5 g of 1-propylsulfonic acid-3-methylimidazolium chloride ionic liquid is added in S1 during the preparation of the cation exchange membrane, and other operations and conditions remain unchanged.
[0107] Experimental Example 1- Initial Performance Test of Bipolar Membrane Stack
[0108] The bipolar membranes prepared in the above examples and comparative examples were subjected to performance tests, and the performance test parameters and corresponding test methods are as follows:
[0109] Unit processing capacity:
[0110] Where:
[0111] PC—unit processing capacity, Kg acid / base (h·m 2 );
[0112] A—Effective area of membrane stack, m 2 ;
[0113] n—number of membrane pairs in the membrane stack;
[0114] M—molar mass of acid or base, g / mol;
[0115] V t —Acid-base endpoint volume, L;
[0116] C t—Acid and base endpoint concentration, mol / L;
[0117] t—running time, s;
[0118] Unit processing energy consumption:
[0119] Where:
[0120] W—unit processing capacity, Kwh / t acid / alkali;
[0121] —The average value of two adjacent voltages,
[0122] —The average value of two consecutive recorded voltages,
[0123] M—molar mass of acid or base, g / mol;
[0124] V t —Acid / base endpoint volume, L;
[0125] C t —Acid and base endpoint concentration, mol / L;
[0126] Δt—time interval between two adjacent times, s;
[0127] Current efficiency:
[0128] Where:
[0129] η—current efficiency, %;
[0130] F—Faraday constant 96485, C / mol;
[0131] —The average value of two consecutive recorded voltages,
[0132] n—logarithm of membrane stack;
[0133] V t —Acid-base endpoint volume, L;
[0134] C t —Acid and base endpoint concentration, mol / L;
[0135] Δt—time interval between two adjacent times, s;
[0136] Water dissociation voltage of bipolar membrane: 1000A / m 2 Direct current, 1 mol / L OH on one side of the cation exchange layer of the bipolar membrane - , the cation exchange layer side is 1mol / LH+ The voltage across the bipolar membrane.
[0137] The initial performance of the operation under the sodium sulfate system is shown in Table 1 below.
[0138] Table 1
[0139]
[0140] By comparing the above Examples 1-9 with Comparative Examples 1-2, it can be seen that the addition of specific ionic liquids in the cation exchange layer and the anion exchange layer can maximize the increase in the cation exchange membrane and the anion exchange layer for H + and OH - The selective permeability of the bipolar membrane anion and cation exchange membrane is increased, thereby increasing the upper limit of the concentration of the prepared acid and base. The prepared acid and base do not need to be subsequently concentrated to meet the conditions for reuse, and the effect is significant.
[0141] Experimental Example 2-Life and Stability Performance Test
[0142] The results of long-term operation of the above embodiments and comparative examples are shown in Table 2.
[0143] Table 2
[0144]
[0145]
[0146] From the data in Tables 1-2 above, it can be seen that the present invention can not only improve the acid-base concentration and yield obtained in the application, but also ensure the stability of high-concentration acid-base and the binding capacity of the anion-cation exchange membrane by further optimizing the raw materials of the anion exchange layer and the setting of the process conditions, thereby ensuring the stability of the bipolar membrane application. In addition, the present invention also verifies the effect of other types of metal elements in the metal catalyst layer. After verification, the effect of replacing only the metal elements in the metal catalyst layer is basically the same.
[0147] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A bipolar membrane, characterized in that include: A cation exchange membrane comprises a substrate and a cation exchange layer disposed on at least one surface of the substrate, wherein the cation exchange layer comprises a sulfonated polymer monomer and a sulfonic acid type ionic liquid, wherein the sulfonic acid type ionic liquid accounts for more than 10% of the weight of the sulfonated polymer monomer; The metal catalyst layer is disposed on one surface of the substrate so that the two opposite surfaces of the substrate are respectively a cation exchange layer and a metal catalyst layer; The anion exchange layer is arranged on the surface of the metal catalyst layer, and comprises quaternized imidazole derivatives and quaternary ammonium ionic liquids, wherein the quaternary ammonium ionic liquids account for more than 25% of the weight of the imidazole derivatives.
2. The bipolar membrane according to claim 1, characterized in that The cation exchange layers are arranged on both surfaces of the substrate, and the metal catalyst layer is arranged on the surface of one of the cation exchange layers.
3. The bipolar membrane according to claim 1 or 2, characterized in that The cation exchange layer is made of cross-linked sulfonated polymer monomers mixed with sulfonic acid ionic liquids, and the molar ratio of the sulfonic acid ionic liquid to the sulfonated polymer monomer is 1:(7-12), preferably 1:(9-10); And / or, the degree of ammonium of the quaternized imidazole derivative is 40-85%; And / or, the mesh number of the substrate is 120-260 mesh; And / or, the loading amount of the metal catalyst layer on the substrate is 0.5-5 g / m 2 , preferably 1-1.5g / m 2 ; And / or, the anion exchange layer has a thickness of 30-80 μm.
4. The bipolar membrane according to any one of claims 1 to 3, characterized in that The sulfonic acid ionic liquid is selected from one or more of 1-propylsulfonic acid-3-methylimidazolium chloride and 1-propylsulfonic acid-3-vinylimidazolium chloride; And / or, the sulfonated polymer monomer is a sulfonated polystyrene monomer; And / or, the quaternary ammonium ionic liquid is selected from one or more of butyltrimethylammonium chloride, hexyltrimethylammonium chloride, propyltrimethylammonium bromide, tetrapropylammonium hydrogen sulfate, tetraoctylammonium bromide and butyltriethylammonium bromide; and / or, the imidazole derivatives include 2-methyl-1-vinylimidazole or 1,2-dimethylimidazole; And / or, the substrate is selected from any one of nylon mesh, PET mesh, PP mesh, PVC mesh, and PE mesh; And / or, the catalyst in the metal catalyst layer is a metal salt, preferably a water-soluble metal salt, more preferably a water-soluble metal chloride; preferably, the metal element in the metal catalyst layer includes one or more of titanium, tin, chromium, cobalt, nickel, platinum, silver, or ruthenium.
5. The method for preparing a bipolar membrane according to any one of claims 1 to 4, characterized in that: include: Preparation of cation exchange membrane: preparing the raw materials of cation exchange layer into membrane-building liquid, preparing the membrane-building liquid on at least one side of the substrate, taking it out, drying and polymerizing it, and cooling it to obtain the cation exchange membrane; Preparation of the metal catalyst layer: preparing the raw materials for preparing the metal catalyst layer into a suspension, evenly applying the suspension on the other side of the cation exchange membrane with the cation exchange layer, and drying to obtain the metal catalyst layer; Preparation of anion exchange layer: prepare the raw materials of anion exchange layer into anion membrane material, attach the anion membrane material to the metal catalyst layer, and obtain a bipolar membrane through ultraviolet light initiation and / or hot pressing reaction.
6. The method according to claim 5, characterized in that In the preparation steps of the cation exchange membrane, the raw materials of the cation exchange layer include sulfonated polymer monomers, solvents, crosslinking agents and sulfonic acid ionic liquids; and / or, the membrane-building liquid is attached to the substrate by immersion; and / or, the drying polymerization process is: first volatilizing at 25-30°C and humidity ≤55% for more than 5 hours, and then drying, preferably, the drying conditions are 100-120°C and more than 24 hours; In the preparation step of the metal catalyst layer, the raw materials of the metal catalyst layer include metal salt, quaternary ammonium and acid solution; the preparation process of the suspension liquid is: the metal salt is added with acid solution to coordinate with the quaternary ammonium in a weakly acidic environment of pH 3-5, and the suspension liquid is obtained after ultrasonic treatment; and / or, the suspension liquid is applied on the cation exchange membrane by ultrasonic spraying; and / or, the drying conditions are 100-120°C and 1.5-2h; In the preparation step of the anion exchange layer, the raw materials of the anion exchange layer include imidazole derivatives, quaternary ammonium reagents, solvents and quaternary ammonium ionic liquids; the ultraviolet light initiation time is 1-10 minutes; the pressure of the hot pressing reaction is 0.1-0.4MpaG and the temperature is 100-130°C.
7. The method according to claim 6, characterized in that In the preparation step of the cation exchange membrane, the crosslinking agent is selected from one or more polyvinylbenzenes, preferably one or more divinylbenzene, trivinylbenzene, divinyltoluene, and divinylethylbenzene; the total amount of the crosslinking agent is 5-15wt% of the mass of the sulfonated polymer monomer; the amount of the solvent is 1-3 times the total mass of the sulfonic acid ionic liquid and the crosslinking agent; the immersion time is 2-8min; In the step of preparing the metal catalyst layer, the acid solution is an inorganic acid, the quaternary ammonium comprises trimethylpropylammonium bromide, the ultrasonic spraying uses a fan-shaped ultrasonic atomizing nozzle or a vortex-type ultrasonic atomizing nozzle, the input gas source pressure of the ultrasonic spraying is 0.5-0.8Mpa, and the operating speed is less than 900mm / s; In the preparation step of the anion exchange layer, the content of the mixture of the imidazole derivative and the quaternary ammonium agent is 15-50% of the solvent content, preferably 15-35%; the quaternary ammonium agent includes any one of bromopropane, chloropropane, iodomethane, and 1,4-dichlorobutane; and / or the molar ratio of the quaternary ammonium ionic liquid to the imidazole derivative is 1:(5-12); The solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, preferably N,N-dimethylacetamide.
8. The method for using the bipolar membrane according to any one of claims 1 to 4, characterized in that: include: The bipolar membrane is installed in a three-compartment bipolar membrane electrodialysis membrane device or a two-compartment electrodialysis device together with an anion exchange membrane and a cation exchange membrane for application in the fields of lithium extraction from salt lakes, waste salt resource recovery, material purification or recovery of organic acids and alkalis.
9. The method of use according to claim 8, characterized in that: In a three-compartment bipolar membrane electrodialysis device or a two-compartment electrodialysis device, the current density during use is 400-1000A / m 2 , and / or, the concentration of the salt chamber is maintained between 2.5-1.1N, and / or, the operating pressure is <0.1MPa, and / or, the operating temperature is 25-45°C, preferably 30-40°C, and / or, the membrane surface flow rate during operation is 3-9cm / s.
10. The method of use according to claim 9, characterized in that: Before operation, the bipolar membrane is activated under the action of an electric field and then washed with water; preferably, during the activation, the current density is 400-1000A / m 2 , activation time is 0.5-5h.
Citation Information
Patent Citations
Technology for adopting bipolar membrane electrodialysis for preparing beta-aminopropionic acid
CN109851515A
A process for preparing β-aminopropionic acid using bipolar membrane electrodialysis
CN109851515B
Perfluorinated bipolar membrane and preparation method thereof
CN116036889A
Preparation method of anion / cation exchange layer cross-linked bipolar membrane
CN118059689A
Bipolar film and its preparing process
CN1250681A
Cited By
Bipolar membrane for producing high-purity acid-base and preparation method thereof
CN120679350A
Novel composite bipolar membrane for preparing low-carbon alcohol alkali metal salt and electrodialysis process thereof
CN121695718A